574 lines
18 KiB
TeX
574 lines
18 KiB
TeX
% !TeX root = ../../script.tex
|
|
\documentclass[../../script.tex]{subfiles}
|
|
|
|
\begin{document}
|
|
\section{Linear Differential Equation Systems}
|
|
|
|
\begin{defi}
|
|
Let $I$ be an open interval, and $A: I \rightarrow \realn^{n \times n}$, $b: I \rightarrow \realn^n$.
|
|
Then the ODES
|
|
\[
|
|
y' = A(x)y + b(x)
|
|
\]
|
|
is said to be a linear differential equation system. If $b$ is the zero function, then the system is homogeneous (otherwise it's inhomogeneous).
|
|
If $A(x) = \const.$, then the system is said to have constant coefficients.
|
|
\end{defi}
|
|
|
|
\begin{rem}
|
|
\begin{enumerate}[(i)]
|
|
\item By using substitution we can transform the equation
|
|
\[
|
|
y^{(n)} = a_{n-1}(x) y^{(n-1)} + a_{n-2}(x) y^{(n-2)} + \cdots + a_0 y + b(x)
|
|
\]
|
|
into the system
|
|
\begin{align*}
|
|
y_{n-1}' &= a_{n-1}(x) y_{n-2} + a_{n-2}(x) y_{n-3} + \cdots + a_0 y + b(x) \\
|
|
y_1 &= y' \\
|
|
y_2 &= y_1' \\
|
|
&~~\vdots \\
|
|
y_{n-1} &= y_{n-2}'
|
|
\end{align*}
|
|
|
|
\item Let $y, z$ be solutions of $y' = A(x) y + b(x)$, then $y - z$ is the solution of the related homogeneous equation $y' = A(x)y$.
|
|
This follows from
|
|
\begin{align*}
|
|
(y - z)'(x) &= A(x)y(x) + b(x) - (A(x)z(x) + b(x)) \\
|
|
&= A(x) (y - z)(x)
|
|
\end{align*}
|
|
\end{enumerate}
|
|
\end{rem}
|
|
|
|
\begin{lem}[Grönwall's Lemma]
|
|
Let $I$ be an open interval, $x_0 \in I$, $y: I \rightarrow [0, \infty)$ continuous, $a, b \ge 0$ and
|
|
\[
|
|
y(x) \le a + b \abs{\int_{x_0}^x y(t) \dd{t}}
|
|
\]
|
|
Then
|
|
\[
|
|
y(x) \le a e^{b\abs{x - x_0}}
|
|
\]
|
|
\end{lem}
|
|
\begin{proof}
|
|
Here we only prove $x > x_0$, but the proof for $x \le x_0$ works analogously.
|
|
Let $\epsilon > 0$ be arbitrary and choose
|
|
\begin{equation}
|
|
z(x) := a + \epsilon + b \int_{x_0}^x y(t) \dd{t}
|
|
\end{equation}
|
|
Then
|
|
\begin{equation}
|
|
z'(x) = by(x) \le bz(x) ~~\forall x \in I
|
|
\end{equation}
|
|
And since
|
|
\begin{equation}
|
|
z(t) \ge a + \epsilon > 0
|
|
\end{equation}
|
|
we get
|
|
\begin{align}
|
|
\int_{x_0}^x \frac{z'(t)}{z(t)} \dd{t} &\le b(x - x_0) \\
|
|
\int_{x_0}^x \frac{z'(t)}{z(t)} \dd{t} &= \ln(x) - \ln(z)
|
|
\end{align}
|
|
Due to the monotony of the exponential function
|
|
\begin{equation}
|
|
z(x) \le z(x_0) e^{b(x - x_0)} = (a + \epsilon) e^{b(x - x_0)}
|
|
\end{equation}
|
|
So
|
|
\begin{equation}
|
|
y(x) \le z(x) \le (a + \epsilon) e^{b(x - x_0)} \le a e^{b(x - x_0)} ~~\forall x \in I
|
|
\end{equation}
|
|
\end{proof}
|
|
|
|
From now on $I$ will always be an open interval, and
|
|
\begin{align*}
|
|
A: I &\rightarrow \realn^{n \times n} \\
|
|
b: I &\rightarrow \realn^n
|
|
\end{align*}
|
|
are continuous, $x_0 \in I$ and $y_0 \in \realn$.
|
|
|
|
\begin{cor}
|
|
The IVP
|
|
\begin{align*}
|
|
y' = A(x)y + b(x) && y(x_0) = y_0
|
|
\end{align*}
|
|
has a unique maximal solution that is defined on all of $I$.
|
|
\end{cor}
|
|
\begin{proof}
|
|
\begin{equation}
|
|
\begin{split}
|
|
f: I \times \realn^n &\longrightarrow \realn^n \\
|
|
(x, y) &\longmapsto A(x) y + b(x)
|
|
\end{split}
|
|
\end{equation}
|
|
We need to show that $f$ fulfils a local Lipschitz condition in $y$.
|
|
Let $(x_1, y_1) \in I \times \realn^n$. Choose a compact $I_1$ such that $x_1 \in I_1 \subset I$.
|
|
Then $A(x)$ is bounded on $I_1$, i.e.
|
|
\begin{equation}
|
|
\exists L > 0: ~~\norm{A(x)} \le L ~~\forall x \in I_1
|
|
\end{equation}
|
|
And then $\forall (x, y), (x, z) \in I_1 \times \realn^n$
|
|
\begin{equation}
|
|
\norm{f(x, y) - f(x, z)} = \norm{A(x)(y - z)} \le \norm{A(x)}\norm{y - z} \le L \norm{y - z}
|
|
\end{equation}
|
|
So $f$ fulfils a local Lipschitz condition, and thus there exists a unique maximal solution.
|
|
Let $a, b \in \realn \cup \set{-\infty, \infty}$ such that $y: (a, b) \rightarrow \realn^n$ is the maximal solution.
|
|
Assume $b \in I$ (so $y$ isn't defined on all of $I$). Then there exists $M, K > 0$ such that $\norm{A(x)} \le M$ and $\norm{b(x)} \le K$ and $[x_0, b]$ and
|
|
\begin{equation}
|
|
\begin{split}
|
|
\norm{y(x)} = \norm{y_0 + \int_{x_0}^x y'(t) \dd{t}} &= \norm{y_0 + \int_{x_0}^x A(t)y(t) + b(t) \dd{t}} \\
|
|
&\le \norm{y_0} + \int_{x_0}^x \norm{A(t)}\norm{y(t)} \dd{t} + \int_{x_0}^x \norm{b(t)} \dd{t} \\
|
|
&\le \norm{y_0} + K(b - x_0) + M\int_{x_0}^x \norm{y(t)} \dd{t}
|
|
\end{split}
|
|
\end{equation}
|
|
Applying Grönwall's Lemma onto $\norm{y(t)}$ yields
|
|
\begin{equation}
|
|
\norm{y(x)} \le \left(\norm{y_0} + K(b - x_0)\right) e^{M\abs{x - x_0}} \le \left(\norm{y_0} + K(b - x_0)\right) e^{M(b - x_0)}
|
|
\end{equation}
|
|
and thus $y$ is bounded on $[x_0, b)$.
|
|
So none of the conditions from \Cref{thm:837} are satisfied, and therefore $b \notin I$.
|
|
This mean that $y$ is defined up to the right boundary of $I$.
|
|
\end{proof}
|
|
|
|
\begin{rem}
|
|
One can show that for linear systems, the Picard iteration leads to a solution that converges on all of $I$. This would lead to an alternative proof.
|
|
\end{rem}
|
|
|
|
\begin{cor}
|
|
Let $y, z: I \rightarrow \realn^n$ be solutions of the ODES
|
|
\[
|
|
y' = A(x)y + b(x)
|
|
\]
|
|
Then the following are equivalent
|
|
\begin{enumerate}[(i)]
|
|
\item $y(x) = z(x) ~~\forall x \in I$
|
|
\item $y(x_0) = z(x_0)$
|
|
\item $y(x) = z(x) ~~\text{ for some } x \in I$
|
|
\end{enumerate}
|
|
\end{cor}
|
|
\begin{proof}
|
|
$(i) \implies (ii)$, $(ii) \implies (iii)$ is trivial.
|
|
To prove $(iii) \implies (i)$, let $x_1 \in I$ such that $y_1 = y(x_1) = z(x_1)$.
|
|
Then $y, z$ are solutions to the IVP
|
|
\begin{align}
|
|
y' = A(x)y + b(c) && y(x_1) = y_1
|
|
\end{align}
|
|
Since this problem has unique solutions
|
|
\begin{equation}
|
|
y = z
|
|
\end{equation}
|
|
must hold.
|
|
\end{proof}
|
|
|
|
\begin{thm}
|
|
The solution set of the homogeneous ODES
|
|
\[
|
|
y' = A(x)y
|
|
\]
|
|
so
|
|
\[
|
|
V := \set[y'(x) = A(x) y(x) ~~\forall x \in I]{y: I \rightarrow \realn^n}
|
|
\]
|
|
is an $n$-dimensional linear subspace of $C^1(I, \realn^n)$.
|
|
\end{thm}
|
|
\begin{proof}
|
|
Proving that $V$ is a vector space is trivial.
|
|
So let $e_1, \cdots, e_n$ be a basis of $\realn^n$ and let $y_i$ be the unique solutions of the initial value problem
|
|
\begin{align*}
|
|
y' = A(x) y && y(x_0) = e_i ~~i \in \set{1, \cdots, n}
|
|
\end{align*}
|
|
Then $y_1, \cdots, y_n$ is a basis of $V$.
|
|
To prove their linear independence, let $\alpha_1, \cdots, \alpha_n \in \realn$ such that
|
|
\begin{equation}
|
|
\alpha_1 y_1 + \cdots + \alpha_n y_n = 0
|
|
\end{equation}
|
|
then
|
|
\begin{equation}
|
|
\alpha_1 y_1(x_0) + \cdots + \alpha_n y_n(x_0) = \alpha_1 e_1 + \cdots + \alpha_n e_n = 0
|
|
\end{equation}
|
|
Since the $e_1, \cdots, e_n$ are linear independent
|
|
\begin{equation}
|
|
\alpha_1 = \alpha_2 = \cdots = \alpha_n = 0
|
|
\end{equation}
|
|
To prove that the $y_1, \cdots, y_n$ span $V$, set $z \in V$ and choose $\alpha_1, \dots, \alpha_n \in \realn$ such that
|
|
\begin{equation}
|
|
\alpha_1 e_1 + \alpha_2 e_2 + \cdots + \alpha_n e_n = z(x_0)
|
|
\end{equation}
|
|
Then the $z$ and $\alpha_1 y_1 + \cdots + \alpha_n y_n$ are maximal solutions of the ODES that are equal in $x_0$. Thus
|
|
\begin{equation}
|
|
z = \alpha_1y_1 + \cdots + \alpha_n y_n
|
|
\end{equation}
|
|
\end{proof}
|
|
|
|
\begin{defi}
|
|
A basis $y_1, \cdots, y_n$ of $V$ is said to be a fundamental system of the ODES
|
|
\[
|
|
y' = A(x) y
|
|
\]
|
|
Analogously, $n$ linearly independent solutions of the equation
|
|
\[
|
|
y^{(n)} = a_{n-1}(x) y^{(n-1)} + a_{n-2}(x) y^{(n-2)} + \cdots + a_0 y
|
|
\]
|
|
are said to be a fundamental system.
|
|
\end{defi}
|
|
|
|
\begin{eg}
|
|
Consider the inhomogeneous equation
|
|
\[
|
|
y' = \sin(x)y + \sin(x)\cos(x)
|
|
\]
|
|
First, find the solutions to the homogeneous equation
|
|
\[
|
|
\frac{y'}{y} = \sin(x)
|
|
\]
|
|
This can be done via integration
|
|
\begin{align*}
|
|
\int \frac{y'(t)}{y(t)} \dd{t} &= -\cos(x) + c \\
|
|
\ln y + c &= -\cos(x) + c
|
|
\end{align*}
|
|
Then the solution is
|
|
\[
|
|
y = K e^{-\cos(x)}
|
|
\]
|
|
The fundamental system in this case is $e^{-\cos x}$.
|
|
We can use a technique called "variation of the constant" to find a solution of the inhomogeneous equation. Define
|
|
\[
|
|
y(x) = C(x) e^{-\cos(x)}
|
|
\]
|
|
Deriving this gives
|
|
\[
|
|
y'(x) = C'(x) e^{-\cos(x)} - C(x) \sin(x) e^{-\cos(x)}
|
|
\]
|
|
Resubstituting this into the initial equation yields
|
|
\begin{align*}
|
|
C'(x) e^{-\cos(x)} + \cancel{C(x)\sin(x)e^{-\cos(x)}} &= \cancel{C(x)\sin(x)e^{-\cos(x)}} + \sin(x)\cos(x) \\
|
|
C'(x) e^{-\cos(x)} &= \sin(x)\cos(x) \\
|
|
C'(x) &= \sin(x)\cos(x)e^{\cos(x)} \\
|
|
C(x) &= (1 - \cos(x))e^{\cos(x)}
|
|
\end{align*}
|
|
So the general solution to the ODE is
|
|
\[
|
|
y(x) = 1 - \cos(x) + K e^{-\cos(x)}
|
|
\]
|
|
\end{eg}
|
|
|
|
\begin{thm}
|
|
Let $y_1, \cdots, y_n$ be a fundamental system for $y' = A(x) y$.
|
|
Define an $n \times n$-matrix
|
|
\[
|
|
W(x) := (y_1(x), y_2(x), \dots, y_n(x))
|
|
\]
|
|
Then $W(x)$ is invertible $\forall x \in I$ and
|
|
\begin{align*}
|
|
z: I &\longrightarrow \realn^n \\
|
|
x &\longmapsto W(x) \int_{x_0}^x \inv{W(t)}b(t) \dd{t}
|
|
\end{align*}
|
|
is a solution to the inhomogeneous system
|
|
\[
|
|
y' = A(x)y + b(x)
|
|
\]
|
|
\end{thm}
|
|
\begin{proof}
|
|
According to the prerequisites the $y_1, \cdots, y_n$ are linearly independent, so the $y_1(x), \dots, y_n(x)$ are also linearly independent in $\realn^n$.
|
|
Thus
|
|
\begin{equation}
|
|
\det W(x) \ne 0 \implies W(x) \text{ invertible}
|
|
\end{equation}
|
|
Deriving this yields
|
|
\begin{equation}
|
|
W'(x) = A(x)W(x)
|
|
\end{equation}
|
|
which means the $i$-th column of this equation is $y_i'(x) = A(x)y_i(x)$.
|
|
Deriving $z$ gives us
|
|
\begin{equation}
|
|
\begin{split}
|
|
z'(x) &= W'(x) \int_{x_0}^x \inv{W(t)} b(t) \dd{t} + W(x)\inv{W(x)} b(x) \\
|
|
&= A(x) z(x) + b(x)
|
|
\end{split}
|
|
\end{equation}
|
|
To apply the fundamental theorem, $W(t)b(t)$ should be continuous.
|
|
The mapping $A \mapsto \inv{A}$ is continuous on $Gl(n)$ (space of invertible matrices).
|
|
\end{proof}
|
|
|
|
\begin{eg}
|
|
Consider the system
|
|
\begin{align*}
|
|
u' = v + \sin(x) && v' = -u + \cos(x)
|
|
\end{align*}
|
|
The homogeneous system in this case is
|
|
\[
|
|
\begin{pmatrix}
|
|
u \\ v
|
|
\end{pmatrix}'
|
|
=
|
|
\begin{pmatrix}
|
|
0 & 1 \\ -1 & 0
|
|
\end{pmatrix}
|
|
\begin{pmatrix}
|
|
u \\ v
|
|
\end{pmatrix}
|
|
\]
|
|
The fundamental system is
|
|
\begin{align*}
|
|
y_1(x) = \begin{pmatrix}
|
|
\sin \\ \cos
|
|
\end{pmatrix}(x)
|
|
&&
|
|
y_2 = \begin{pmatrix}
|
|
\cos \\ -\sin
|
|
\end{pmatrix}(x)
|
|
\end{align*}
|
|
Then define
|
|
\begin{align*}
|
|
z(x) &= C_1(x)y_1(x) + C_2(x)y_2(x) \\
|
|
&= \underbrace{\begin{pmatrix}
|
|
\sin(x) & \cos(x) \\
|
|
\cos(x) & -\sin(x)
|
|
\end{pmatrix}}_{W(x)}
|
|
\begin{pmatrix}
|
|
C_1(x) \\ C_2(x)
|
|
\end{pmatrix}
|
|
\end{align*}
|
|
Deriving this yields
|
|
\begin{align*}
|
|
z'(x) &= C_1'(x)y_1(x) + \cancel{C_1(x)y_1'(x)} + C_2'(x)y_2(x) + \cancel{C_2(x)y_2'(x)} \\
|
|
&= \cancel{C_1(x)Ay_1(x)} + \cancel{C_2(x)Ay_2(x)} + b(x) \\
|
|
&= b(x)
|
|
\end{align*}
|
|
This can be explicitly solved
|
|
\begin{align*}
|
|
C_1'(x)\sin(x) + C_2'(x)\cos(x) &= \sin(x) \\
|
|
C_1'(x)\cos(x) - C_2'(x)\sin(x) &= \cos(x)
|
|
\end{align*}
|
|
Leading to
|
|
\begin{align*}
|
|
C_1'(x) &= C_1'(x)(\sin^2(x) + \cos^2(x)) = \sin^2(x) + \cos^2(x) = 1 \\
|
|
C_2'(x) &= C_2'(x)(\cos^2(x) - \sin^2(x)) = 0
|
|
\end{align*}
|
|
Thus
|
|
\begin{align*}
|
|
C_1(x) &= x \\
|
|
C_2(x) &= 0
|
|
\end{align*}
|
|
So the general solution of the homogeneous equation is
|
|
\[
|
|
y_h = \begin{pmatrix}
|
|
x \sin(x) \\ x \cos(x)
|
|
\end{pmatrix}
|
|
\]
|
|
Our next goal is to find a solution of $y' = Ay$ with $A \in \realn^{n \times n}$ constant.
|
|
In one dimension the solution would be
|
|
\[
|
|
y = Ce^{Ax}
|
|
\]
|
|
Does this also hold for $n > 1$?
|
|
\end{eg}
|
|
|
|
\begin{rem}
|
|
Let $A \in \realn^{n \times n}$
|
|
\[
|
|
e^{Ax} = \sum_{k=0}^{\infty} \rec{k!}(Ax)^k = \sum_{k=0}^{\infty} \rec{k!} A^k x^k
|
|
\]
|
|
We have
|
|
\[
|
|
\sum_{k=0}^{\infty} \rec{k!} \norm{A^k x^k} \le \sum_{k=0}^{\infty} \frac{\abs{x}^k}{k!} \norm{A}^k = e^{\norm{x}\norm{A}} < \infty
|
|
\]
|
|
Thus, $e^{Ax}$ is defined $\forall A \in \realn^{n \times n}, ~\forall x \in \realn$. Deriving this yields
|
|
\[
|
|
\dv{x}e^{Ax} = \sum_{k=1}^{\infty} \rec{k!} A^k x^{k-1} = A \sum_{k=1}^{\infty} \rec{(k-1)!} A^{k-1} x^{k-1} = Ae^{Ax}
|
|
\]
|
|
\end{rem}
|
|
|
|
\begin{thm}
|
|
Let $A \in \realn^{n \times n}$. The IVP
|
|
\begin{align*}
|
|
y' = Ay && y(x_0) = y_0
|
|
\end{align*}
|
|
is solved exactly by
|
|
\[
|
|
y(x) = e^{A(x - x_0)}y_0
|
|
\]
|
|
\end{thm}
|
|
\begin{proof}
|
|
Without proof.
|
|
\end{proof}
|
|
|
|
\begin{rem}
|
|
\begin{enumerate}[(i)]
|
|
\item The problem of solving IVPs can be reduced to a problem of calculating a matrix exponential.
|
|
\item The following does NOT generall hold
|
|
\begin{align*}
|
|
\dv{t}e^{A(x)} &= A'(x) e^{A(x)} \\
|
|
e^{A + B} &= e^A e^B
|
|
\end{align*}
|
|
\item Let $v$ be an eigenvector of $A$ to the eigenvalue $\lambda$. Then
|
|
\begin{align*}
|
|
e^{Ax} v = \left(\sum_{k=0}^{\infty} \rec{k!} A^k x^k\right) v &= \sum_{k=0}^{\infty} \frac{x^k}{k!} A^k v \\
|
|
&= \left(\sum_{k=0}^{\infty} \frac{x^k}{k!} \lambda^k\right) v = e^{\lambda x} v
|
|
\end{align*}
|
|
\end{enumerate}
|
|
\end{rem}
|
|
|
|
\begin{eg}
|
|
Consider the IVP
|
|
\begin{align*}
|
|
\begin{pmatrix}
|
|
y \\ z
|
|
\end{pmatrix}'
|
|
= \underbrace{\begin{pmatrix}
|
|
0 & 1 \\ 1 & 0
|
|
\end{pmatrix}}_A
|
|
\begin{pmatrix}
|
|
y \\ z
|
|
\end{pmatrix}
|
|
&& y_0 = \begin{pmatrix}
|
|
1 \\ 0
|
|
\end{pmatrix}
|
|
\end{align*}
|
|
This $A$ is diagonalizable and has the eigenvalues
|
|
\begin{align*}
|
|
\lambda_1 = -1 && \lambda_2 = 1
|
|
\end{align*}
|
|
and the eigenvectors
|
|
\begin{align*}
|
|
v_1 = \begin{pmatrix}
|
|
1 \\ 1
|
|
\end{pmatrix}
|
|
&&
|
|
v_2 = \begin{pmatrix}
|
|
1 \\ -1
|
|
\end{pmatrix}
|
|
\end{align*}
|
|
So we can solve this ODES by calculating
|
|
\begin{align*}
|
|
e^{Ax} y_0 = e^{Ax} \cdot \frac{1}{2}(v_1 + v_2) &= \frac{1}{2}\left(e^{\lambda_1 x} v_1 + e^{\lambda_2 x} v_2\right) \\
|
|
&= \frac{1}{2} \left(e^x v_1 + e^{-x} v_2\right)
|
|
\end{align*}
|
|
And thus
|
|
\begin{align*}
|
|
y(x) = \frac{1}{2} \left(e^x + e^{-x}\right) && z(x) = \frac{1}{2} \left(e^x - e^{-x}\right)
|
|
\end{align*}
|
|
\end{eg}
|
|
|
|
\begin{rem}
|
|
Often the process above is formulated as follows:
|
|
Start by defining
|
|
\[
|
|
y(x) = c \cdot e^{\lambda x} v ~~c, \lambda \in \field \text{ and } v \in \realn
|
|
\]
|
|
Insert this into the ODE
|
|
\[
|
|
c\lambda e^{\lambda x} = c e^{\lambda x} Av
|
|
\]
|
|
So $\lambda$ is an eigenvalue of $A$ to the eigenvector $v$.
|
|
\end{rem}
|
|
|
|
\begin{thm}
|
|
Let $A \in \realn^{n \times n}$ be diagonalizable, and $v_1, \cdots, v_n$ is a basis of eigenvectors to the eigenvalues $\lambda_1, \cdots, \lambda_n$.
|
|
Then the functions
|
|
\[
|
|
y_i(x) = e^{\lambda_i x} v_i ~~i \in \set{1, \cdots, n}
|
|
\]
|
|
are a fundamental system to the ODES
|
|
\[
|
|
y' = Ay
|
|
\]
|
|
\end{thm}
|
|
\begin{proof}
|
|
We have
|
|
\begin{equation}
|
|
e^{Ax} v_i = e^{\lambda_i x} v_i
|
|
\end{equation}
|
|
In $x = 0$ the
|
|
\begin{equation}
|
|
y_1(0) = v_1, ~y_2(0) = v_2, ~\cdots, ~y_n(0) = v_n
|
|
\end{equation}
|
|
are linearly independent, so the $y_1, \cdots, y_n$ are also linearly independent.
|
|
\end{proof}
|
|
|
|
\begin{rem}
|
|
\begin{enumerate}[(i)]
|
|
\item There is a special case, where $A \in \realn^{n \times n}$ is not diagonalizable in the real number space, but in the complex number space.
|
|
Let $\lambda = \lambda_r + \lambda_i$ be the eigenvalue to the eigenvector $v = v_r + v_i$. Then
|
|
\begin{gather*}
|
|
e^{\lambda_r x} (v_r \sin(\lambda_i x) + v_i \cos(\lambda_i x)) \\
|
|
e^{\lambda_r x} (v_r \cos(\lambda_i x) + v_i \sin(\lambda_i x))
|
|
\end{gather*}
|
|
be linearly independent, real-valued solutions. To solve the IVP
|
|
\begin{align*}
|
|
y(x) = C e^{\lambda x} v && y(0) = y_0
|
|
\end{align*}
|
|
we want to transform it into an eigenvalue problem and find a solution to that. Doing that gives us
|
|
\[
|
|
y(x) = C_1 e^{\lambda_1 x} v_1 + \cdots + C_n e^{\lambda_n x} v_n
|
|
\]
|
|
By inserting the initial condition we can find
|
|
\[
|
|
C_1 v_1 + C_2 v_2 + \dots + C_n v_n = y_0
|
|
\]
|
|
Finding the $C_1, \cdots, C_n$ shows us that the solution is automatically real.
|
|
|
|
\item If $A$ is not diagonalizable one can try and bring $A$ into Jordan normal form.
|
|
\end{enumerate}
|
|
\end{rem}
|
|
|
|
\begin{eg}
|
|
Consider the IVP
|
|
\begin{align*}
|
|
\begin{pmatrix}
|
|
y \\ z
|
|
\end{pmatrix}'
|
|
=
|
|
\begin{pmatrix}
|
|
0 & 1 \\ -1 & 0
|
|
\end{pmatrix}
|
|
\begin{pmatrix}
|
|
y \\ z
|
|
\end{pmatrix}
|
|
&&
|
|
y_0 = \begin{pmatrix}
|
|
1 \\ 0
|
|
\end{pmatrix}
|
|
\end{align*}
|
|
The eigenvalues and eigenvectors are
|
|
\begin{align*}
|
|
\lambda_1 &= i & \lambda_2 &= -i \\
|
|
v_1 &= \begin{pmatrix}
|
|
1 + i \\ -1 + i
|
|
\end{pmatrix}
|
|
&
|
|
v_2 &= \begin{pmatrix}
|
|
1 - i \\ -1 - i
|
|
\end{pmatrix}
|
|
\end{align*}
|
|
Thus we have the general solution
|
|
\[
|
|
C_1 e^{ix} v_1 + C_2 e^{-ix} v_2
|
|
\]
|
|
which expands to
|
|
\begin{align*}
|
|
(i + 1) C_1 \cancel{e^{i0}} + (1 - i)C_2 \cancel{e^{-i0}} &= 1 \\
|
|
(i - 1) C_1 \cancel{e^{i0}} + (-1 - i)C_2 \cancel{e^{-i0}} &= 0
|
|
\end{align*}
|
|
and solves to
|
|
\begin{align*}
|
|
C_1 = \frac{1}{4} (1 - i) && C_2 = \frac{1}{4} (1 + i)
|
|
\end{align*}
|
|
So the solution to the IVP is
|
|
\begin{align*}
|
|
y(x) = \cos(x) && z(x) = -\sin(x)
|
|
\end{align*}
|
|
\end{eg}
|
|
|
|
\begin{thm}
|
|
Let $a_1, \cdots, a_{n-1} \in \cmpln$. Let $\lambda_1, \cdots, \lambda_k$ be the roots of the polynomial
|
|
\[
|
|
a_0 + a_1 \lambda + \cdots + a_{n-1} \lambda^{n-1} + \lambda^n
|
|
\]
|
|
and $\nu_1, \cdots, \nu_k$ their multiples. Then the functions
|
|
\[
|
|
x \longmapsto x^l e^{\lambda_i x} ~~i \in \set{1, \cdots, k}, l \in \set{0, \cdots, \nu_{i_1}}
|
|
\]
|
|
form a fundamental system for
|
|
\[
|
|
a_0 y + a_1 y' + \cdots + a_{n-1} y^{(n-1)} + y^{(n)}
|
|
\]
|
|
\end{thm}
|
|
\end{document} |